Stress and Mental Health Issues: An Age Related Study among Women Employees: Exploring the impact of aging process on stress perception and mental health among working women (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Stress and its effect, have been central topics of interest of researchers, since Stress is worldwide phenomenon, seen across all areas of life and among all age groups. Stress has both harmful physical and emotional responses. Due to changes in society many women prefer working women still have to perform their traditional role or duties at home which in turn increase the stress, balancing the responsibilities at work and home is making women more stressed and has an impact on their mental health. The present study aims to study the effect of aging process on perception of stress and their mental health. A study was conducted on 300 women employees working in Bangalore. Their occupational stress was assessed by administering occupational stress index developed by A. K. Srivastava and A. P. Singh. Their personal stress was assessed using Singh’s personal stress source inventory developed by Arun Kumar Singh (2004). Their mental health was assessed by using employee mental health inventory developed by Dr. Jagdesh. A Suitable stastical technique was used to analyzes the obtained results